Hypoxic ischemic encephalopathy (HIE) - Sánchez-Rodríguez, E. Cuauhtémoc; López, Vasthi J. (Frontiers in Neurology, 2024)
The morbidity and mortality of acute ischemic hypoxic encephalopathy of the newborns have not been dramatically modified in the last 20 years. The review has the purpose to describe the use of hyperbaric oxygenation (HBOT) in the management of acute ischemic hypoxic encephalopathy of the newborn.Review of the medical literature of the use of HBOT in the pathophysiology of this condition and how it modifies the result of the patients treated in an early stage.When HBO2 is administered in a timely and prompt manner, it can promote the survival of the penumbra, modulate the cytokine storm, modify the inflammatory cascades, restore mitochondrial function, inhibit apoptosis, reinstate cellular communication and cytoskeleton function, reinstall the functioning of the kinase system, reduce the cytotoxic and tissue edema, promotes the microcirculation, and promote an antioxidant effect. All these secondary mechanisms help to save, rescue, and protect the marginal tissue.When use promptly, HBOT is a noninvasive adjunct treatment that can preserve the marginal tissue caused by ischemia, hypoxia, maintain the metabolic needs of the penumbra, reduce the inflammatory cascades, avoid extension of the damage tissue, and modulate the ischemia reperfusion injury.